2019
DOI: 10.18632/oncotarget.26578
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative MRI-radiomics features improve prediction of survival in glioblastoma patients over MGMT methylation status alone

Abstract: BackgroundGlioblastoma (GBM) is the most common malignant central nervous system tumor, and MGMT promoter hypermethylation in this tumor has been shown to be associated with better prognosis. We evaluated the capacity of radiomics features to add complementary information to MGMT status, to improve the ability to predict prognosis.Methods159 patients with untreated GBM were included in this study and divided into training and independent test sets. 286 radiomics features were extracted from the magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 45 publications
2
45
0
Order By: Relevance
“…The segmentation was generated from FLAIR images and the segmented volumes were then utilized on T1WI CE . We chose to segment on FLAIR because we found that the inclusion of the FLAIR hyperintense tumoral and peritumoral lesion (usually larger than the contrast enhanced lesion) helps the radiomic features quantify the strength of tumor edges on T1WI CE . Moreover, texture matrices used for the extraction of radiomic features were computed using the 3DVOI as is commonly done with PET/CT images.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The segmentation was generated from FLAIR images and the segmented volumes were then utilized on T1WI CE . We chose to segment on FLAIR because we found that the inclusion of the FLAIR hyperintense tumoral and peritumoral lesion (usually larger than the contrast enhanced lesion) helps the radiomic features quantify the strength of tumor edges on T1WI CE . Moreover, texture matrices used for the extraction of radiomic features were computed using the 3DVOI as is commonly done with PET/CT images.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, skewness of the Gabor edge maps was found to have a very low robustness in this study. Yet in a previous study, high negative skewness of Gabor edges was identified as a biomarker to differentiate patients with GBM by survival, and with a threshold of −0.49 it misclassified only <3% of the patients in this study, using I MC segmentation. Similarly, high robustness should not be used as a criterion to select features.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations